The impact of pre-school on young children's cognitive attainments at entry to reception - Sammons, P; Elliot, K; Sylva, K; Melhuish, E; Siraj-Blatchford, I; Taggart, B (2004)
This article explores the impact of pre-school experience on young children's cognitive attainments at entry to primary school and analyses data collected as part of a wider longitudinal study, the Effective Provision of Pre-school Education (EPPE) project, which followed a large sample of young children attending 141 pre-school centres drawn from six types of provider in five English regions. The article compares the characteristics and attainments of the pre-school sample with those of an additional 'home' sample (children who had not attended pre-school) recruited at entry to reception. Multilevel analyses of relationships between child, parent and home environment characteristics and children's attainments in pre-reading, early number concepts and language skills are presented. Duration of time in pre-school is found to have a significant and positive impact on attainment over and above important influences such as family socio-economic status, income, mother's qualification level, ethnic and language background. The research also points to the separate and significant influence of the home learning environment. It is concluded that pre-school can play an important part in combating social exclusion by offering disadvantaged children, in particular, a better start to primary school.